Putting Islam Hadhari into practice - Abd Razak, Dzulkifli (2006)
IF THERE is a litmus test for the acceptance of the concept of Islam Hadhari, the Islamic Family Act is probably it. The Act deemed controversial by many, not least the women’s groups, was passed by the Parliament recently though it is yet to be gazetted. Going by the 10 principles of Islam Hadhari, one would be surprised to find on at least three points there seems to be a "violation" of the principles as posted on its official website, http://www.islam.gov.my/islamhadhari/concept.html. The first point is the principle of free and independent people (rakyat berjiwa merdeka). Among the characteristics of these people is that they are creative and innovative. Independent people are able to produce dynamic and positive ideas, which are beneficial for the promotion of individuals, families, society and country.